2014
DOI: 10.1177/0898264314541696
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation in an Older U.S. Chinese Population

Abstract: Suicidal ideation was common among U.S. Chinese older adults in the Greater Chicago area. Further longitudinal studies should be conducted to explore the risk and protective factors associated with suicidal ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…Given the fact that most study participants were white, this finding supports existing literature that suggested altruistic suicidesas a rare phenomenon in Western culture (Lester, 1994;Dong, Chen, Wong & Simon, 2014;Zhao, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…Given the fact that most study participants were white, this finding supports existing literature that suggested altruistic suicidesas a rare phenomenon in Western culture (Lester, 1994;Dong, Chen, Wong & Simon, 2014;Zhao, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…A total of 40.9% participants reported feelings of hopelessness. In a sample of Chinese hospitalized cancer patients, the prevalence for hopelessness was 64.4% [25]. This higher prevalence may be due to the nature of a clinical sample of terminal cancer samples.…”
Section: Discussionmentioning
confidence: 94%
“…Among the participants who reported hopelessness, 58.8% were female; the majority has received education less than 12 years (78.5%), and with income less than $10,000 (85.6%). Compared to the group without any hopelessness, the group with hopelessness symptoms had a significantly greater proportion of older adults being widowed (25 Beck hopelessness scale -7 reliability and content validity…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Indeed, studies of suicide often focus on actual suicide attempts as well as suicide ideation (Harwood & Jacoby, 2000). Therefore, any individual expressing suicidal thoughts or intentions must be treated with caution (Dong, Chen, Wong, & Simon, 2014;Park et al, 2014); therefore, it is crucial to gain a better understanding of suicide ideation among the elderly and the factors that are related to suicide ideation in this population.…”
Section: Introductionmentioning
confidence: 99%